Analysis of strategic innovation capability development of Singapore SMEs - Yu, Hao (2008)
The emergence of the knowledge economy, intense global competition and considerable technological advance has seen innovation become increasingly central to competitiveness. Innovation is diverse and pervasive. It is applicable to every facet of business activity of each enterprise.